Ready for the future? A survey on open access with scientists from the French National Research Center (CNRS). Issue 4 (21st November 2016) - Schöpfel, Joachim; Ferrant, Coline; André, Francis; Fabre, Renaud
Abstract : Purpose: This paper aims to present empirical evidence on the opinion and behaviour of French scientists (senior management level) regarding open access (OA) to scientific and technical information. Design/methodology/approach: The results are part of a nationwide survey on scientific information and documentation with 432 directors of French public research laboratories conducted by the French National Research Center (CNRS) in 2014. Findings: The CNRS senior research managers (laboratory directors) globally share the positive opinion towards OA revealed by other studies with researchers from the UK, Germany, the USA and other countries. However, they are more supportive of open repositories (green road) than of OA journal publishing (gold). The response patterns reveal a gap between generally positive opinions about OA and less supportive behaviours, principally publishing articles with article processing charges (APCs). A small group of senior research managers does not seem to be interested in green or gold OA and reluctant to self-archiving and OA publishing. Similar to other studies, the French survey confirms disciplinary differences, i.e. a stronger support for self-archiving of records and documents in HAL by scientists from Mathematics, Physics and Informatics than from Biology, Earth Sciences and Chemistry; and more experience and positive feelings with OA publishing and payment of APCs in Biology than in Mathematics or in Social Sciences and Humanities. Disciplinary differences and specific French factors are discussed, in particular in the context of the new European policy in favour of Open Science. Originality/value: For the first time, a nationwide survey was conducted with the senior research management level from all scientific disciplines. The response rate was high (>30 per cent), and the results provide good insight into the real awareness, support and uptake of OA by senior research managers who provide both models (examples for good practice) and opinion leadership.